The relationship between assets under management and mutual fund performance. Does size matter? A South African investigation - Mandlazi, Tsepo (Department of Finance and Tax, 2023)
This study investigates whether there is a potential relationship between mutual fund size and mutual fund performance using South African data. Academic studies on the relationship between mutual fund size and mutual fund performance has produced inconclusive results to date, with five potential outcomes being found, namely no relationship, a positive, a negative, a U-shaped, or an inverted Ushaped relationship. Using monthly gross and net of fee data from two mutual fund categories as defined by The Association for Savings and Investment South Africa “ASISA”, namely equity (ASISA category South African EQ General) and multi-asset high equity (ASISA category South African MA Equity), the ten year period from 2011 to 2020 was analysed. Additional to traditional risk-adjusted performance measures and unlike any previous South African studies, the study made use of performance measures based on well-known multi-factor asset pricing models. Furthermore, the potential for non-linearities in the relationship between mutual fund size and performance was also for the first time taken into consideration in the South African context with the inclusion of a quadratic equation in the regression specifications. Following a portfolio approach or ranking analysis, regression techniques were used to test for linear and quadratic relationships between mutual fund size and performance measures. The regression analysis based on the portfolio approach found that there is a convex quadratic or Ushaped relationship between South African mutual fund performance and mutual fund size. The relationships were also found to be statistically significant. The findings of the study imply that there is an intermediate mutual fund size range (between approximately R43 million and R2.6 billion) where the trade-off between benefits of economies of scale (larger funds) and the flexibility to take more active equity positions and be nimbler in execution (smaller funds), can result in lower-than-average risk-adjusted fund performance. Furthermore, the results show that size is an important fund characteristic in understanding the continued performance of mutual funds in South Africa and can assist investors in choosing which mutual fund they can invest in.